The growth of graphene on nickel thin films - Sabki, Syarifah Norfaezah (2012)
The growth of graphene on Ni thin films using several different methods is discussed. These methods include no intentional introduction of carbon, immersion in an organic solvent, exposure to carbon-containing gas and a solid state approach by decomposition of molecules. All the methods have produced single layer graphene over a large area. We suggest that the graphene formation without intentional introduction of carbon involves conversion of carbon-containing adsorbates on Si02. This process has been verified by our experiment of graphene growth by decomposition of C6O, in which C60 is deposited on top of Si02 and buried under Ni thin film. Single layer graphene has successfully formed which suggests that the carbon from C60 has diffused and segregated to the top of the Ni surface. So we investigate the effect of outgassing aimed to eliminate adsorbates on Si02. Graphene growth by immersion in an organic solvent was initially performed to investigate the effect of outgassing process, and single layer graphene is formed but is highly defective, as determined by the intensity of the Raman D band. We found that outgassing the Si02 is important to produce single layer graphene, but the defects in graphene are not significantly reduced. Graphene growth method using propylene is carried out to identify the factors that influence the amount of defects and to reduce through optimization of growth parameters. The graphene defects are reduced significantly by varying the annealing temperature and exposure time to propylene. We found that different Ni thickness do not affect the defect formation in graphene but do improve the Ni surface morphology. Graphene growth by decomposition of C60 on Ni thin film produced graphene layers with controlled thickness. This molecular carbon source provides a method of controlling the total dosage of carbon introduced into the film with a high degree of precision. We found that the C60 coverage, annealing temperature, and deposition sequence influence the properties of graphene layers. We also presented preliminary results of graphene enhanced Raman scattering (GERS) of adsorbed PTCDI. We demonstrate that single layer graphene is a very good substrate for Raman enhancement in which the adsorbed molecules can be detected at a small fraction of monolayer coverage. Using the same transfer method typically used for graphene, we managed to transfer PTCDI on graphene from Ni film to Si02. Here we demonstrate the effect of a substrate for graphene which can give rise to the enhancement of a Raman signal of adsorbed molecules.